PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI KASUS DI KABUPATEN KEPULAUAN TALAUD) - Soleman, Muhammad T.; Pontoh, Winston; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
This study aims to examine the factors that influence the disclosure of local government financial statements. The population in this study are employees who work in the Regional Development Planning Agency (BAPPEDA) in the Talaud Islands Regency. Data collection techniques using questionnaires. The type of data used is primary data collected by sending questionnaires to respondents. The research method is quantitative, while the analysis technique used is multiple linear regression analysis. This research result shows that Audit Findings and Capital Expenditures affect the disclosure of regional government financial statements, while the balance funds do not have an influence on the disclosure of local government financial statements.